2009
DOI: 10.1098/rstb.2009.0083
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of eyes and visually guided behaviour

Abstract: The morphology and molecular mechanisms of animal photoreceptor cells and eyes reveal a complex pattern of duplications and co-option of genetic modules, leading to a number of different light-sensitive systems that share many components, in which clear-cut homologies are rare. On the basis of molecular and morphological findings, I discuss the functional requirements for vision and how these have constrained the evolution of eyes. The fact that natural selection on eyes acts through the consequences of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
220
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(230 citation statements)
references
References 91 publications
1
220
1
8
Order By: Relevance
“…Our data also shed light on another aspect of eye evolution. It has been proposed that major steps in eye evolution, such as implementation of spatial resolution and true optics, have been tightly connected to the acquisition of new visually guided behaviours [30]. It is suggested that early in eye evolution, animals possessed few and simple visually guided behaviours, requiring only simple eyes and simple nervous systems.…”
Section: (D) Navigationmentioning
confidence: 99%
“…Our data also shed light on another aspect of eye evolution. It has been proposed that major steps in eye evolution, such as implementation of spatial resolution and true optics, have been tightly connected to the acquisition of new visually guided behaviours [30]. It is suggested that early in eye evolution, animals possessed few and simple visually guided behaviours, requiring only simple eyes and simple nervous systems.…”
Section: (D) Navigationmentioning
confidence: 99%
“…Colley and Dowling 2 pressures on visually guided behavior that favored one path at the expense of another (Nilsson & Arendt, 2008 ;Nilsson, 2009 ).…”
Section: Spotlight On the Evolution Of Visionmentioning
confidence: 99%
“…A sequence of stages has been envisioned to explain how a primitive eyespot evolved to become a complex camera-type eye (Nilsson & Arendt, 2008 ;Nilsson, 2009 ). In multicellular organisms, these fl at eyespots can be simple single-cell photoreceptors, scattered on the surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations